Reproductive biology of Rhaphiodon vulpinus (Ostariophysi: Cynodontidae) in the Tocantins River Basin, Brazil - Neuberger,Andréa L. (2007)
In order to evaluate aspects of the reproductive biology of Rhaphiodon vulpinus in the Upper and Middle Tocantins River, samples were taken monthly from October, 1999 through September, 2001, by means of gill nets. Males, which were more abundant than females (chi2 146.87: df=1: p<0.05), matured at a smaller size. The reproductive period of the species extended essentially from November through January, with a peak of activity in November. Fecundity, with an estimated mean value of 98,185 oocytes, varied from 38,177 to 215,841 oocytes, and it did not correlate with the length of the individual female analyzed (r=0.4663: p=0.206). Relative fecundity was 130.6 oocytes/g total weight. Mature oocytes had a mean diameter of 0.98 mm, corresponding to a volume of 0.50 mm³.